Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan, Dan Kepemilikan Manajerial Terhadap Manajemen Laba Pada Perusahaan Barang Konsumen Primer Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2020 - Hani Prisela Oktaviani; Nurul Asfiya; Moermahadi Soerja Djanegara (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
The case of the Covid-19 pandemic for two years has had an impact, one of which is the economy of both the country, society and companies. Many companies have decreased revenue so that it directly affects profit, even some companies go bankrupt. So that this pandemic condition can trigger the emergence of earning management actions carried out by the company so that the financial statements presented look good. The number of cases that occur in companies due to earning management practices, makes company actors do various ways to minimize the payment of corporate taxes. The case of earning management is done by reporting profits or profits that are not too large, so that it has an impact on the lack of tax payments. This research aims to: 1) To find out the effect of Tax Planning on Earnings Management on primary consumer goods companies listed on the Indonesia Stock Exchange in 2018-2020 period; 2) To find out the effect of Deferred Tax Expense on Earnings Management on primary consumer goods companies listed on the Indonesia Stock Exchange in 2018-2020 period; 3) To find out the effect of Managerial Ownership on Earnings Management on primary consumer goods companies listed on the Indonesia Stock Exchange in 2018-2020 period; 4) To find out Tax Planning, Deferred Tax Expense, and Managerial Ownership simultaneously on Earning Management Management in primary consumer goods companies listed on the Indonesia Stock Exchange in 2018-2020 period. This research method uses multiple linear regression analysis with quantitative methods. The population in this study was 87 primary consumer companies listed on the Indonesia Stock Exchange in 2018-2020. The number of samples used is 36 samples with sample withdrawal using purposive sampling. The data source in this study used secondary data obtained from each company's annual report and then the data was processed using SPSS version 26. Partial test results (Test t) show that the Tax Planning variable has no effect on Earning Management, the Deferred Tax Expense variable has an effect on Earning Management, and the Managerial Ownership variable has an effect on Earning Management. Simultaneous test results (Test F) show that all independent variables namely Tax Planning, Deferred Tax Expense, and Managerial Ownership collectively affect Earning Management. Keywords: Tax Planning, Deferred Tax Expense, Managerial Ownership, Earning Management